-20g+7(3h+3g)-14h=0

Simple and best practice solution for -20g+7(3h+3g)-14h=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20g+7(3h+3g)-14h=0 equation:


Simplifying
-20g + 7(3h + 3g) + -14h = 0

Reorder the terms:
-20g + 7(3g + 3h) + -14h = 0
-20g + (3g * 7 + 3h * 7) + -14h = 0
-20g + (21g + 21h) + -14h = 0

Combine like terms: -20g + 21g = 1g
1g + 21h + -14h = 0

Combine like terms: 21h + -14h = 7h
1g + 7h = 0

Solving
1g + 7h = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-7h' to each side of the equation.
1g + 7h + -7h = 0 + -7h

Combine like terms: 7h + -7h = 0
1g + 0 = 0 + -7h
1g = 0 + -7h
Remove the zero:
1g = -7h

Divide each side by '1'.
g = -7h

Simplifying
g = -7h

See similar equations:

| 8x=41-(1-3x) | | 2(1x+10)=10 | | c=.90c | | (7y-6)-(3y+8)= | | 5x-3-4x=-12 | | 2x-4(x-4)=-5+4x-9 | | 4(b-2)=12 | | 129.19=2.25h+71.19 | | -5[(3x+1)-(4x-2)]=6(6-x)-4 | | 6(1-6x)+5(-x-8)= | | 9y-29=-69+4y | | (1+w)(5w+7)=0 | | 10m+7=27 | | 6(3-2x)=30 | | 7s-10=2+s | | 4m-4=16 | | 7(y+3)=9y+23 | | 5x-10=275 | | 10+2(-4)= | | X^6+19x=216 | | -5(4x+7)=185 | | 4x^2-15=4x | | 3x+35=2x+205 | | 4x+5+3x+8=90 | | 0.80x+.05(20-x)=.10(-80) | | 8x-20=28 | | -x+3=-15 | | -7x-4=-25 | | 10a-3(4a+b)+2(a-7b)=0 | | -3(5x-7)=-84 | | -2(3x+3)-2(2-x)=3(4x+3)-1 | | 6x+14=6x |

Equations solver categories